A comparative study on patent term extension for pharmaceutical patent / Nur Atiqah Razali, Muhammad Fakkurullah Roslan and Hafizul Hakim Abdul Hamid - Razali, Nur Atiqah; Roslan, Muhammad Fakkurullah; Abdul Hamid, Hafizul Hakim (2013)
This project paper discusses on the various system of pharmaceutical patent term extension from different countries and the situation of pharmaceutical patent term extension in Malaysia. Chapter one of this research study present a background about the laws and issues about the pharmaceutical patent term extension. Chapter two of this research discusses the situation of patent term extension in Malaysia which includes the necessity of having patent term extension and also the implication resulting from the system. In chapter three, this research discusses on the various system of patent term extension for pharmaceutical patent in selected countries which are United States, European Union, Australia, Japan, Singapore, South Korea and Taiwan. The analysis of the patent term extension can be seen through the comparative table which includes different elements in the system for example requirement for granting the extension, reasons for introduction of extension and maximum effective patent life. In the final chapter, this research laid down the recommendation and the proposed system of pharmaceutical patent term extension to be implemented in Malaysia.